ERANAN ERGONOMI PADA TRANPORTASI PASIEN DI RUMAH SAKIT - ., Zulfiwati; Pardede, Nelson (JURNAL GAUNG INFORMATIKA, 2015)
Hospitals are currently experiencing increasingly fierce competition with the increasing number of existing hospitals, so hospitals are required to be more competentby improving existing services, such as providing the best health services to the public and oriented to individual health. Each type and place of work has a different risk ofdanger. This is influenced by location, work process, work material, and tools used in carrying out the work. One of the high-risk jobs is a hospital. In general, people andworkers in hospitals are less aware of the various potential hazards that exist. "Occupational illnesses in hospitals can attack all workers, both medical and nonmedical personnel" (Anies, 2005: 123). Transfer techniques to clients are included in patient transport, such as transferring patients from one place to another, either using transport equipment such as ambulances, and tankers that are useful as carriers of emergency patients. Patients who are hospitalized at the hospital will definitely experience the process of movingfrom the treatment room to another room such as for medical check-ups, operating rooms, etc. This will result in the risk of low back points for both patients and nurses. Patient transportation is in accordance with hospital ergonomics which can be divided into two, transport patients for emergency and critical care and also equipmentneeded such as troly which is easy to push for drug storage and place reports / patient development records in accordance with the place that has been provided in the trolydesign. Besides that the hospital floor must follow the standards that have been determined in accordance with the needs of the hospital and maintain patients, hospitalstaff and visitors avoid exposure to the disease, and be safe from workplace accidents when carrying out transportation between hospital rooms.